2013
DOI: 10.1016/j.laa.2012.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Note on the spectral characterization of some cubic graphs with maximum number of triangles

Abstract: Cubic graphs of given order with maximum number of triangles are characterized. Consequently, it is proved that certain cubic graphs with maximum number of triangles are determined by their adjacency spectrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In [36], it have been shown that this graph is also DQS. Remark 5 Some 3-regular DAS graphs are given in [31,43]. We can obtain DQS graphs with independent edges and isolated vertices and isolated vertices from Corollary 3.4.…”
Section: Resultsmentioning
confidence: 99%
“…In [36], it have been shown that this graph is also DQS. Remark 5 Some 3-regular DAS graphs are given in [31,43]. We can obtain DQS graphs with independent edges and isolated vertices and isolated vertices from Corollary 3.4.…”
Section: Resultsmentioning
confidence: 99%
“…Remark 3.5. Some 3-regular DS graphs are given in [9,14,25]. We can obtain DQS graphs with isolated vertices from Theorem 3.13.…”
Section: Theorem 32mentioning
confidence: 99%